The Effectiveness of Group Guidance With Role-Playing Techniques to Reduce the Negative Impact of Smartphones - Matahari Citra Prabawani Nurul Aisyah; Meila Dwi Nurmala; Bangun Yoga Wibowo (Department of Guidance and Counseling, FIP, Undiksha, 2023)
A smartphone is a form of technological development that can now assist various processes in human life, such as communicating, shopping, obtaining information, and learning. Students who use smartphones excessively tend to show negative behavior, such as decreased focus and learning outcomes. This study aims to determine the effectiveness of group counseling with the role-playing technique to reduce the negative impact of smartphones on class IX students of junior high school. This research belongs to the type of experimental research, with a total sample of 66 students of class IX junior high school. Sampling in this study was carried out using a purposive sampling technique so that the final sample was obtained, eight students in the high category as the research sample. The data collection technique uses a questionnaire, an instrument for smartphones' negative impact. The data obtained in the study were then analyzed using analytical techniques using the Wilcoxon signed rank test. The results showed a decrease from 77% to 62%. Based on these results, group guidance with role-playing techniques effectively reduces the negative impact of students' smartphones.